1895
DOI: 10.5962/bhl.title.53809
|View full text |Cite
|
Sign up to set email alerts
|

The American lobster; a study of its habits and development

Abstract: Although the lobster has a place in the literature of the Old World, it is seldom mentioned by American writers. Eathbun, who was the first to give a history of the American lobster fisheries, says that the great abundance and rare flavor of the lobster "are not infrequently mentioned in the early annals of New England, and it probably formed an important element in the food-supply of the seacoast inhabitants of colonial times. As a separate industry, however, the lobster fishery does not date back much, if an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
129
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 31 publications
3
129
0
Order By: Relevance
“…Ontogeny of the foregut and STNS Although previous developmental studies in lobsters have focused on Homarus americanus (Bumpus, 1891;Herrick, 1895;Factor, 1981;Charmantier, 1987;Charmantier and Aiken, 1987), recent comparative developmental work has shown that H. americanus and H. gammarus share similar morphological and anatomical features (Gruffydd et al, 1975). In H. gammarus, as in other decapod crustaceans (Bumpus, 1891;Regnault, 1972), the future foregut appears as a depression of the ectoderm followed by its invagination toward the yolk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ontogeny of the foregut and STNS Although previous developmental studies in lobsters have focused on Homarus americanus (Bumpus, 1891;Herrick, 1895;Factor, 1981;Charmantier, 1987;Charmantier and Aiken, 1987), recent comparative developmental work has shown that H. americanus and H. gammarus share similar morphological and anatomical features (Gruffydd et al, 1975). In H. gammarus, as in other decapod crustaceans (Bumpus, 1891;Regnault, 1972), the future foregut appears as a depression of the ectoderm followed by its invagination toward the yolk.…”
Section: Discussionmentioning
confidence: 99%
“…Although the developmental periods of Homarus have been described (Bumpus, 1891;Herrick, 1895;Beltz et al, 1992), there are no reports on the development of the embryonic foregut or stomodeum of lobsters or other large crustaceans. Thus, using histological techniques (see Materials and Methods) we followed the morphological development of the stomodeum which can be detected very early in the embryo of Homarus as an invagination of the ectoderm between the brain and the ventral nerve cord.…”
Section: Ontogeny Of the Foregutmentioning
confidence: 99%
See 1 more Smart Citation
“…The stages are easily distinguished from one another and their development has been described. All four stages are shown in Figure 2 (Herrick, 1896). (Botero and Atema, 1982;Ennis, 1986).…”
Section: Larval Morphology and Developmentmentioning
confidence: 99%
“…This motor system was chosen because its neuronal organization is well understood in adults (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and because it develops largely after larvae hatch from the egg (5,30,31). Swimmeret sense organs and muscles are undifferentiated at hatching, but the appendages are fully developed and capable of rhythmic locomotor movements 3 weeks later, when the larvae molt to the fourth larval stage (5).…”
mentioning
confidence: 99%